AMYLASE ENZYME EXTRACT FROM TAPE YEAST IN A FUNCTIONAL POWDER DRINK: AN INNOVATION FOR INHIBITING POSTPRANDIAL CARBOHYDRATE ABSORPTION - Carissa Almaira Ramadhani; Echa Meizila; Vienno Maraville Zhafin (GoAcademica Research dan Publishing, 2026)
Postprandial fatigue is a common condition experienced after consuming carbohydrate-rich foods such as rice, bread, and noodles. This condition is thought to be related to the slow hydrolysis of starch into glucose. This study aimed to extract and characterize the amylase enzyme from tape yeast (Saccharomyces cerevisiae) and formulate a functional powder drink based on the enzyme extract. Crude enzyme extraction was performed using maceration with distilled water at a 1:2 (w/v) ratio. The extract was then formulated into powder using maltodextrin as a carrier and dried at 40°C. Starch hydrolysis activity was tested in vitro using the Glucose Liquidcolor method at a wavelength of 505 nm. Safety tests included pH measurement, total plate count (TPC), and detection of Escherichia coli and Salmonella sp. The results showed that the amylase enzyme extract from tape yeast was capable of hydrolyzing starch into glucose, with an increase in glucose concentration of 211% compared to the control. The functional powder drink had a pH of 5.1 ± 0.2, a TPC of 1.8 × 10³ ± 2.2 × 10² CFU/g, and no detectable E. coli or Salmonella sp. in 25 g of sample. Organoleptically, the product was acceptable with a taste score of 3.4 out of 5. It is concluded that the amylase enzyme extract from tape yeast exhibits promising starch hydrolysis activity, and the formulated powder drink meets basic food safety standards. Further in vivo studies are required to evaluate the product's effectiveness under physiological conditions.